1D modelling of the NW Sab'atayn Basin Upper Jurassic source rocks, Yemen: Implications for hydrocarbon generation and thermal maturity. Issue 7 (3rd April 2022) - Alsrory, A. S. A. E.; Al‐Azazi, Nabeel A. S. A.; Albaroot, Mohammed; Quasim, M. A.
Abstract : Sab'atayn Basin is considered to be the most petroliferous Mesozoic basin in Yemen, although exploration efforts in the northwestern part of the basin are unproven due to scant drilling activities. In this work one‐dimensional (1D) basin modelling was used to examine the hydrocarbon generation and expulsion history of the Upper Jurassic source rocks using PetroMod 2012.2 software. The geo‐history modelling was applied for the studied wells, and it shows that some stratigraphic units are missing, which adversely affect the tectonics, sedimentary subsidence, burial history, hydrocarbon maturation, and generation. There is a major period of subsidence that occurred in the Upper Jurassic and is manifest in the Kamaran‐01 well. In addition, a second major uplift occurred in the Miocene and had a discernible effect on heat flow distribution as well as burial histories. Reverse heat flow is observed in the Saba‐01 well, where the present heat flow is greater than the palaeo‐heat flow. The beginning of petroleum generation in the Meem and Lam members (Madbi Formation) source units has been predicted to occur during the Late Jurassic, and subsequently occurred in the Lower Cretaceous. Peak expulsion of hydrocarbons from the Meem Member occurred in the Eocene and late Oligocene, while expulsion modelling performed on the Lam Member asserts that it has not reached the phase of oil expulsion. Abstract : Burial plot with temperature history distribution indication maximum burial in Eocene 4832m, best fitting eroded thickness of 900 m, and temperature history ranges from 29 °C to 192 °C for all stratigraphical successions for Kamranan‐01 well. Burial history reconstruction of the Saba‐01 well, as well as temperature history distribution, reveal a continuous sedimentation pattern with no subsidence or uplift event, and burial temperature history varies from 23.79 °C to 178.55 °C for all stratigraphical units.